The climate of Utopia: Victorian hothouses and H. G. Wells - Lund, SE (Indiana University Press, 2023)
In “The Flowering of the Strange Orchid” (1894), The Time Machine (1895), and A Modern Utopia (1905), H. G. Wells criticizes the idea inherited from Thomas More’s Utopia (1516) that ideal climate is static. In “The Flowering of the Strange Orchid” the constant climate of Winter Wedderburn’s steaming greenhouse nearly spells death, while the globally engineered climate in The Time Machine entails the germination of hot-house grotesques. As Wells clarifies in A Modern Utopia, in the modern age when utopia becomes temporal, climate can no longer be imagined as constant. Engaging critically with Victorian hothouse culture, his work sheds light on the fallacy of imagining utopia as a place of eternal sunshine—a fallacy currently reiterated in the sociotechnical imaginary of solar geoengineering.